Keunggulan Kompetitif Berkelanjutan UMKM Di Era Vuca - Mochammad Nafis (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
MSMEs in developing countries, especially in Indonesia, are often associated with conditions of economic problems and also social status, both poverties, the effects of unemployment, income that is not evenly distributed and does not meet daily needs and even development in urban and rural areas as well as urbanization problems. It is hoped that developing MSMEs will present an effective contribution. The purpose of this study is to analyze one of the MSME businesses, namely Korean Street Food in Sidoarjo, East Java. The author wants to analyze the role of MSMEs in the area and also their role in helping the economy. The business offered is in the form of selling Korean-style soup and also Takoyaki which are sold per portion worth ten thousand rupiahs and through these sales can generate a monthly sales turnover of around 9-10 million rupiahs. This is very helpful for the regional economy. The SWOT analysis that has been carried out is good, but the concept of product sales and promotion must be actively improved in digitization to support the VUCA generation.